The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1530/ec-19-0537
|View full text |Cite
|
Sign up to set email alerts
|

Female hyperandrogenism and elite sport

Abstract: Emerging evidence indicates that testosterone, which can increase muscle mass and strength, stimulates erythropoiesis, promotes competitive behaviour, and enhances the physical performance of women. Indeed, the levels of testosterone within the normal female range are related to muscle mass and athletic performance in female athletes. Furthermore, among these athletes, the prevalence of hyperandrogenic conditions, including both polycystic ovary syndrome and rare differences/disorders of sex development (DSD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 72 publications
(106 reference statements)
2
22
0
10
Order By: Relevance
“…Our study showed that the participants’ basal testosterone levels were within the low range of normal testosterone concentrations. This finding is in accordance with previous published data regarding gender-specific differences in sex hormones as a result of ultra-endurance exercise [ 39 , 40 ], and is better explained by the hypometabolic state hypothesis since this endocrine disturbance is characterized by low testosterone levels [ 4 ]. Moreover, in our results, participants with higher testosterone levels showed less strength loss and muscle membrane disruption after ultra-endurance exercise.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that the participants’ basal testosterone levels were within the low range of normal testosterone concentrations. This finding is in accordance with previous published data regarding gender-specific differences in sex hormones as a result of ultra-endurance exercise [ 39 , 40 ], and is better explained by the hypometabolic state hypothesis since this endocrine disturbance is characterized by low testosterone levels [ 4 ]. Moreover, in our results, participants with higher testosterone levels showed less strength loss and muscle membrane disruption after ultra-endurance exercise.…”
Section: Discussionsupporting
confidence: 93%
“…Male sex hormones such as testosterone, dihydrotestosterone, and dehydroepiandrosterone modulate the different physiological mechanisms that are responsible for athletic performance improvement [ 4 , 5 ]. Testosterone binding to the androgen receptor at the surface of the muscle fiber increases calcium release from the intracellular stores, activating different mechanisms that increase the number of muscle fibers and satellite cells, as well as the size of motor neurons [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study provides novel insight regarding the physiological effects of increased circulating testosterone levels on endurance performance in active healthy young women. These results support the body of evidence on the effects of testosterone in women ( Hirschberg et al, 2020 ; Horwath et al, 2020 ) and help to put light on the controversy regarding eligibility regulations in athletes with naturally high testosterone levels and their potential unfair advantage ( Hirschberg, 2020 ).…”
Section: Discussionsupporting
confidence: 78%
“…Since the physiological effects of androgens may be decisive for performance, it is not surprising that androgens have been secretly used for many years to enhance physical performance ( Franke and Berendonk, 1997 ); androgens remain the most common class of doping agents used by athletes ( IAAF, 2020 ). The apparent sex-based differences in athletic performance are largely attributed to the 10–20 times higher circulating levels of testosterone in men than in women ( Handelsman et al, 2018 ; Hirschberg, 2020 ). Therefore, increasing the circulating levels of testosterone may potentially be more beneficial for improving physical performance in women than in men ( Huang and Basaria, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Boys develop stronger arms and wider shoulders, and by eighteen the average boy can throw three times as far as the average girl" (Epstein 2013, 67). Testosterone increases muscle mass and strength, and stimulates the production of red blood cells, so those with higher testosterone levels can use more oxygen than those with less (Hirschberg 2020). "World agegroup records in sprinting are nearly identical for boys and girls at age nine, before puberty, when there is little biological reason for gender segregation in sports.…”
Section: Why Sex Segregation In Sports Continuesmentioning
confidence: 99%